Solve the following exponential equation: `3^(6 - 3x) = 1/27`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to express the term to the right side as 3 raised to a power such that: `27 = 3^3` .

Writing the equation using the powers of 3 yields:

`3^(6-3x)=1/(3^3)`

`` You need to remember that `1/(3^3) = 3^(-3), ` hence:

`3^(6-3x)=3^(-3)`

Notice...

(The entire section contains 2 answers and 132 words.)

Unlock This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial
Approved by eNotes Editorial Team